Behaviour and design of extruded high-strength aluminium alloy SHS beam-columns - Beibei Li; Pengcheng He; Jingfeng Wang; Yuanqing Wang (Sustainable Structures)
An extensive study of beam-columns made from 7A04-T6 aluminum alloy in a square hollow section (SHS) configuration is presented in this paper, integrating both experimental and numerical work to study their flexural buckling behaviour. Eight pin-ended SHS specimens with two extruded SHS profiles - 80×5 and 120 × 10 (in mm), were tested under eccentric compression, along with tests of material coupons and measurements of initial geometric imperfections. The experimental data were employed in the investigation to assess the validity of the numerical model, which was subsequently subjected to a series of parametric analyses aimed at expanding the existing results across a wider spectrum of slenderness ratios, cross-section dimensions, and load combinations. Both experimental and simulated datasets were employed to verify the precision of resistance forecasts for SHS beam-columns by design approaches outlined in European, Chinese and American standards. Findings indicated that both the European and Chinese standards tended to provide relatively conservative predictions for buckling resistances, while the American standard sometimes produced predictions leading to higher risk. Finally, a modification strategy for the design of AA7A04-T6 SHS beam-columns, utilizing modified interaction buckling factors that account for non-dimensional member slenderness and compression resistances, was suggested to enhance the precision and reliability of resistance forecasts.